Tinjauan Kualitas Bakteriologis dan Tingkat Risiko Pencemaran Air Sumur Gali di Kelurahan Sungai Ulin Kota Banjarbaru - Erpan Roebiakto; Gunung Setiadi; Yohannes Joko Supriyadi (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2017)
Humans in meeting the needs of water should pay attention to aspects of quality and quantity. Particularly the aspect of bacteriological quality, because contaminated water can cause waterborne disease. One of the clean water facilities used by the community is the well. The community of Sungai Ulin Kota Banjarbaru uses wells for daily activities. The purpose of this research is to know the bacteriological quality and the level of risk of water pollution wells Sungai Ulin Kelurahan Kota Banjarbaru. The research type is descriptive and cross-sectional research design. The population of this study was all wells in three Rukun Tetangga (RT 19, RT 20 and RT 21) of 40 and samples of bacteriological quality of well good water. The result of the research is the characteristic of respondent from the level of education of most elementary school is 19 (47.5%), knowledge level 21 (52,5%), middle income category (1-3 million / month) 36 (90%) and length of stay Respondents old category (> 10 years) as many as 39 (78%). The conclusion of the study showed that the quality of bacteriologic (MPN Coli) of well water 3 (7.5%) was eligible and 37 (92.5%) were not eligible. The level of risk of contamination of wells to 40 wells, among others, for very high risk of 6 units (15%), high risk of 26 units (65%), medium risk 5 pieces (12.5%) and low risk 3 (7.5%). Need to do research about the relationship of good construction with bacteriological quality of good water.